Risco de desastres por incêndios florestais: um mapeamento do município de Moju (PA) - ALMEIDA, Tarsis Esaú Gomes (Universidade Federal do Pará, 2018)
The objective of the research was to identify areas where there is a greater risk of forest fire disaster in Moju municipality of Pará. The evidence that the use of fire in its territory, the consequences of which may have a significant negative impact on the municipality's cattle ranching, are the support for the choice of location. In this sense, through bibliographic research, documentary, interviews and analyzes, three main maps were constructed. The first was the Forest Fire Hazard Map, in which it was verified which areas would be most likely to suffer from forest fires. The second was the Socioeconomic Assessment Map, whose purpose was to measure the possible demographic, social, cultural, and economic impacts resulting from forest fires in the municipality. The last one was the Forest Fire Disaster Risk Map, which is the product of an algebra of the first two maps. Thus, in the actions of environmental risk management for the municipality, the mapping done will help in the decision making by the managers. Also, the way the mapping was done provides the basis for the formation of a manual that can be used by the Pará Military Fire Brigade in other municipalities.